PENDIDlKAN ISLAM MENUJU MASYARAKAT MADANI - Ajat Sudrajat, Ajat Sudrajat (Jurnal Cakrawala Pendidikan, 2016)
The concept of a civil society which has become a new discourse in the life of a nation has received positive response not only &om the intellectual circles but also from high-ranking government officials in Indonesia, including President BJ Habibi and Minister of Defence and Security, General Wiranto They have even rethorically expressed the idea of a future Indonesia in a civil society format. Therefore, all the nation’s political, social, economic, military, and educational potential is being directed towards such a society. A civil society has at least three characteristics, i e., ( 1 ) the eis a sufficiently high degree of autonomy of ndiv duaalsn d groups in the society in their interaction with the state, (2) there is free public space for the expresslon of individual and group political activity in the society, and (3) there is an individual and group capacity of refiisit g state or gover iiitnntet ventionin the society. Tqlamir rtlt c-atinna .: part of thr national educational potential, has a share in the responsibility of building a civil society. For that, there are characteristics of Islamic educatlon which, in terms of institutional matter, educational process, and educational material, need to undergo reformation. Only 11t.Ins larttic educalior re sult in a self-supporting institutlon and produce human resources prepared to confront life’s challenges and filled with enough tolerant attitude in the face of differences.